GREEN ECONOMY: THE ECONOMIC IMPACT OF CLIMATE CHANGE IN CENTRAL ASIA - Mukhitdinova Muyassar Ziyaviddinovna (American Journals, 2023)
The paper aims at gaining insight into the economic impact of climate change in Central Asian Countries such as Kazakhstan, Kyrgyz Republic, Tajikistan, Turkmenistan, and Uzbekistan. Central Asia is highly vulnerable to climate change owing to a set of critical interactions between the region’s socio-economic and environmental contexts. While some of the Central Asian countries are among the states contributing the least to global greenhouse gas emissions, they are already suffering directly from the effects of climate change. The main aim of the paper was introduction to green economics in Central Asia, much of the region is located in already difficult climate zones, where global warming exacerbates desertification, water stress, and rising sea levels. This trend entails fundamental economic disruptions, endangers food security, and undermines public health, with ripple effects on poverty and inequality, displacement, and conflict. Considering the risks posed by climate change, the central message of this departmental paper is that adapting to climate change by boosting resilience to climate stresses and disasters is a critical priority for the region’s economies.
Keywords: Green economy, climat change, global warming, food security, economic growth